EFFECTS OF PRODUCT QUALITY, PRICE, AND BRAND IMAGE ON THE BUYING DECISION OF CITY CAR PRODUCT - Amron, Amron (Archives of Business Research, 2018)
The study examined the effect of product quality, price, and brand image on buying decision of city car product in Semarang, Indonesia. The primary data was obtained from 100 respondents who had city cars. Surprisingly, from the three independent variables, it was found that the variable of product quality had greater effect compared with those of price and brand image. In other hand, the one with the smallest effect on buying decision was brand image. The study recommends the managements of city car companies to pay attention to the elements of product quality, price and brand in preparing their promotional programs in order to attract more consumers to buy city cars.